Applications of AI: Does it Impact Emissions of Carbon? - Himanshi Pandey (International Journal of Cheminformatics, 2024)
Several countries, including India, have vowed to achieve net-zero emissions by the middle of the century, in line with the Paris Agreement's goals. India, as one of the world's largest and fastest-growing economies and the third-largest carbon emitter, has set lofty goals in its climate change plan. By 2030, India intends to attain carbon peaking, which represents the top of its carbon emissions before beginning a slow drop. Furthermore, the country has committed to reducing emissions by 45% and moving toward carbon neutrality. A key component of India's goal is to transform its energy industry towards sustainability. To this purpose, the government has pledged to increase the amount of renewable energy sources in its overall electric grid capacity to nearly half, with a goal of 50% by 2030. This move is critical not just for reducing carbon emissions, but also for maintaining energy security and spurring economic growth through investments in clean energy. Nonetheless, measuring emissions in India is a substantial difficulty due to varied reporting standards. Unlike some of its rivals, India does not routinely provide detailed emission statistics, making it difficult to track progress toward its climate goals. Bridging the gap in data availability and precision is critical for informed policymaking, resource allocation, and international collaboration in the battle against climate change. To meet its ambitious climate goals, India needs adopt a wide range of policies across several sectors, including energy, transportation, industry, and agriculture. This includes increasing the use of renewable energy, boosting energy efficiency, implementing cleaner industrial processes, and encouraging sustainable land use practices. In conclusion, India's aggressive approach to combating climate change—which includes setting high goals like reaching a carbon peak by 2030, reducing emissions significantly, and shifting to renewable energy sources—underlines its dedication to sustainability. However, reaching these targets will require coordinated actions from the government, business community, and civil society in addition to improve systems for tracking and disclosing emissions data.
Keywords: Carbon neutrality; Carbon peaking; Climate change; Data availability; Economic growth; Emission reductions; Energy transition; India; Monitoring; Net-zero emissions; Paris agreement; Policy; Renewable energy; Sustainability; Targets; mitigation; reporting